Overcoming Gender Gaps in Entrepreneurship Education and Training - Pimpa, Nattavud (Frontiers in Education, 2021)
Entrepreneurship education and training is essential for female entrepreneurs who juggle family expectations, personal life, and new ventures at the same time. Indeed, generic entrepreneurship training may fail to promote understanding in gender literacy and its relationship with creating and managing business entities. To help address gender gaps, this paper explores gender issues in the training process for female entrepreneurs, the researcher collected primary data from 28 trainers through personal interviews and secondary data from the 43 training evaluation forms from trainees who participated in the national entrepreneurship training programs in Thailand. The researcher identifies three themes that are related to gender gaps and effectiveness in the entrepreneurship training context. They include (1) gender mainstreaming, (2) gender-sensitive training approaches, and (3) the adoption of proper technology and innovation for female entrepreneurs. Secondary data also confirm that female entrepreneurs in this study address the need for professional development that promotes them to engage in gender competencies, technology, and innovation for new ventures. The opportunity for professional development can be limited by family and social commitments. Engaging with experienced female entrepreneurs and business role models can promote understanding in the three areas among female entrepreneurs. This paper outlines a novel approach in synergizing gender issues, training, and entrepreneurship skills. It concludes with some explanations of the relative efficacy of entrepreneurship training that reduces gender gaps for female entrepreneurs.